Book Review: The Early Reception of Manga in the West - Cetoria Tomberlin (Journal of Anime and Manga Studies, 2024)
Book review of art history and manga scholar Martin de la Iglesia's The Early Reception of Manga in the West, published in 2023 by Christian A. Bachmann Verlag Press in Berlin.